Pathologic splenic rupture in a patient with follicular lymphoma - Aniruddha P Dayama; Rajan Kapoor; Jasmita Dass; Gurmeet Singh; Manoranjan Mahapatra; Haraprasad Pati (Mediterranean Journal of Hematology and Infectious Diseases)
Follicular lymphoma (FL) is the most common indolent Non Hodgkin’s lymphoma (NHL) . It presents primarily with widespread disease which may be asymptomatic and involves the bone marrow in around 40% of patients . Although the disease is widespread at presentation the incidence of complications such as splenic rupture which are usually seen with other aggressive lymphomas is rare